Reemergence of Endemic Chikungunya, Malaysia - AbuBakar, Sazaly; Sam, I-Ching; Wong, Pooi Fong; Hooi, Poh Sim; Roslan, Nuruliza; Mat Rahim, Nor Aziyah (Centers for Disease Control and Prevention, 2007)
Chikungunya virus infection recently reemerged in Malaysia after 7 years of nondetection. Genomic sequences of recovered isolates were highly similar to those of Malaysian isolates from the 1998 outbreak. The reemergence of the infection is not part of the epidemics in other Indian Ocean countries but raises the possibility that chikungunya virus is endemic in Malaysia.